Extending the use of existing CAD software to enable visualization of solar penetration in complex building forms - McMinn, Terrance; Karol, Elizabeth (EarthScan, 2010)
Currently available computer-aided design (CAD) software packages used by architects and designers are limited in their ability to provide visual images of solar penetration into complex building forms. However, in order to better design for thermal impact, it would be helpful for professionals and students to be able to visualize solar penetration at various times of the day and in various seasons. A comparative study of three CAD software packages used by designers was carried out to ascertain the barriers within the software in providing visual images of solar penetration. The study showed that typical CAD tools used by architects and designers were not well adapted to display solar penetration into complex building forms. However, this article shows that images of solar penetration can be produced in a timely manner using free-for-use software. This production of sun patches on arbitrary projection planes is an innovative process that delivers web-based output.